Effect of age on total lipid and cholesterol of hen eggs - OLOYO, R A (The Indian Journal of Animal Sciences, 2014)
Duplicate groups each of 50O laying hens of 2 age group 5 (6 and 20 months old) were used to study the effecd of age on total lipid and cholesterol of eggs. The laying hens’were fed with a practical-type layer’s ralion and were maintained under commercial egg pmduclion conditions. Average egg weight. yolk weight, tolal lipid (g) and total lipid (mg/g yolk) were significantly (P<0.05) higher in the older birds, whereas, cholesterol(mg), cholesterol (mg/gyolk) and cholesterol (mg/g total lipid) were higher( (P<0.05) in the younger birds. While egg sire and yolk weight were positively but not signiticantly correlated (P>0.05) with the total lipid (g), both parameters were negatively and significantly correlated (P<0.05) with total lipid and cholesterol expressed as fractions or yolk weight.